A fuzzy-logic-controlled two-speed electromagnetic gearbox for electric vehicles - Rahman, Mohammed Ataur; Sany, Ihsan; Hassan Bakri, Nurul Huda (Faculty of Engineering, Universitas Indonesia, 2022)
Epicyclic transmission (ET), five-speed manual gearbox (5-SMT), automatic transmission (AT), and continuously variable transmission (CVT) are all possible transmission options for electric vehicles (EVs). The ET is so complex that motorists may be unaware that they are in gear. As the 5- SMT, AT, and CVT transistors are heavier, they consume more energy. Although a single-speed gearbox is lighter, it is not capable of developing enough torque for acceleration. Therefore, this study presents a fuzzy-logic-controlled electromagnetic two-speed gearbox (AEM-2SGB) model for EVs. The electromagnetic actuator is modelled in terms of electromagnet size, number of coil turns, supply current, and electromagnetic force needed to shift gears. The parametric analysis of AEM- 2SGB is conducted using Matlab Simulink and a fuzzy simulation model. According to the results, the AEM-2SGB has a first-gear shift time of 110 ms at 300 Nm motor torque and a second-gear shift time of 116 ms at 110 km/h vehicle speed, with a maximum current supply of 16 A using a 24 V lithium ion battery. The AEM-2SGB reduces weight by 37%-66%, transmission losses by 40%–90%, and battery life by 5%.